A Comprehensive Overview of Organ Inflammatory Responses: Genesis, Possible Mechanisms, and Mediators of Inflammation - Samar A. Antar; Ayman M. Mahmoud; Walied Abdo; Cherry Gad; Ahmed A. Al-Karmalawy (Tabriz University of Medical Sciences, 2023)
An immune system response known as inflammation can be carried on by a variety of things, such as infections, damaged cells, and noxious substances. These factors may cause acute or chronic inflammatory responses in the heart, pancreas, liver, kidney, lungs, brain, colon, and reproductive system, which may cause disease or tissue damage. Inflammatory cells and signaling pathways are activated by both pathogenic and non-pathogenic agents, cell injury, and infectious agents. The most ubiquitous types of these include tumor necrosis factor-alpha (TNF-α), nuclear factor kappa B (NF-κB), High mobility group box 1 protein (HMGB1), mitogen-activated protein kinase (MAPK), monocyte chemoattractant protein (MCP1), interleukin 1 beta (IL1β), and Janus kinase-signal transducer and activator of transcription (JAK-STAT). Severe inflammation has the potential to cause systemic inflammatory response syndrome. The most severe forms of this condition are characterized by hyperinflammation and can cause organ damage, shock, and even death. We concentrate on the origin of inflammation, all conceivable inflammatory mechanisms, and organ-specific inflammatory responses in this study on inflammatory reactions inside organs.